Rectangular Microstrip Antenna Vs Dipole Antenna for Wi-Fi Application - Wong, Alan; Tan, Yang (IEEE, 2013)
Presently all the commercially available Wi-Fi is using a dipole antenna due to its wide radiation coverage. This paper compares the performance of the normal dipole antenna with the performance of the rectangular microstrip antenna in term of radiation pattern and data rate achievable for a typical WiFi application.